ИНСАН ҚƏДИРИ – УЛЛЫ ҚƏДИРИЯТ - Алланазарова, Б. (FAN va JAMIYAT, 2019)
In the scientific article is considered the value and role of personality in the society. There are points of view of west philosophy about the impact factors of individuality in a personality.